Four-Meter Gait Speed Cut-off and Correlation with 6-Minute Walk Test in Adults - Nury Nusdwinuringtyas; Tresia Fransiska; Peggy Sunarjo; Kevin Triangto; Febrian Santausa; M. Sopiyudin Dahlan (Faculty of Medicine, Universitas Padjadjaran, 2022)
In facilities where a track required is not available for gait speed test, a simpler method using a shorter track and test duration is needed. One of such methods is the 4-meter gait speed. This study aimed to determine the cut off values for 4MGS and its correlation with the 6-minute walk test (6MWT), a more common functional performance test with shorter track and time. Data for this study were collected at the Department of Rehabilitation of Dr. Cipto Mangunkusumo General Hospital during the period of August 2016 to March 2017. The consecutive sampling approach was used to recruit healthy Indonesian adults (n=61) aged 18–50 years into this cross sectional study. The anthropometric and respiratory variables were measured as descriptive data and the cut-off values were determined by calculating the mean 4-meter gait speed (4MGS)-2SD for each gender. The 6MWT was performed afterwards to assess the correlation between 4MGS and 6-minute walk distance (6MWD). Results presented a mean 4MGS value of 2.114±0.309 m/s (male) and 1.908±0.227m/s (female) with the cut-off values for normal gait speed of 1.496 m/s and 1.454m/s for male and female, respectively. Factors affecting 4MGS were body height, body weight, forced vital capacity (FVC), and forced expiratory volume in 1 second (FEV1). The 4MGS is only shown to be weakly correlated with 6MWD (r=0.314, p=0.014). The cut-off values for 4MGS can be used as a reference to assess the normality of gait speed as a parameter of functional mobility in healthy Indonesian adults and should be used in adjunct to 6MWT to represent a comprehensive functional capacity status.